2022
DOI: 10.1002/elps.202100348
|View full text |Cite
|
Sign up to set email alerts
|

Global intercompany assessment of ICIEF platform comparability for the characterization of therapeutic proteins

Abstract: An international team spanning 19 sites across 18 biopharmaceutical and in vitro diagnostics companies in the United States, Europe, and China, along with one regulatory agency, was formed to compare the precision and robustness of imaged CIEF (ICIEF) for the charge heterogeneity analysis of the National Institute of Standards and Technology (NIST) mAb and a rhPD-L1-Fc fusion protein on the iCE3 and the Maurice instruments. This information has been requested to help companies better understand how these instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…It has been demonstrated that these differences do not affect the separation efficiency, so that the different icIEF instruments currently available provide comparable results. 16 , 17 In both systems, pI values of the sample are determined after calibration with pI-markers, assuming a linear dependence throughout the pH gradient.…”
Section: Challenges Of Establishing a Cief Procedures Universally App...mentioning
confidence: 99%
“…It has been demonstrated that these differences do not affect the separation efficiency, so that the different icIEF instruments currently available provide comparable results. 16 , 17 In both systems, pI values of the sample are determined after calibration with pI-markers, assuming a linear dependence throughout the pH gradient.…”
Section: Challenges Of Establishing a Cief Procedures Universally App...mentioning
confidence: 99%
“…CIEF and iCIEF have matured into techniques that are routinely applied in analytical laboratories, especially in the biopharmaceutical industry. Exemplary applications include, but are not limited to, monoclonal antibodies [192,[209][210][211][212][213][214][215], bispecific antibodies [216][217][218], ADCs [219,220], PEGylated proteins [221,222], glycoproteins, in particular erythropoietin [213,223,224], and fusion proteins [213,225]. Because this subsection is part of the former "proteins" section, which was extended to all biopharmaceuticals, it should not go unmentioned that the range of applications has been expanded beyond proteins and includes oligosaccharides [226], LNPs and related mRNA vaccines [227][228][229][230], virus-like particles [231,232], poliovirus [230,233], adeno-associated virus [230,[234][235][236][237], papillomavirus [238], and bacteria and yeast cells [230].…”
Section: Cief and Iciefmentioning
confidence: 99%
“…For iCIEF, RSD values ≤0.8% for the apparent pI values and ≤11% (outliers removed) for the percentage area were reported [209]. A recent intercompany study using two iCIEF instruments reported RSDs values ≤0.28% for the apparent pI and RSDs values ≤6.25% for the percentage area of NISTmAb [215]. Kahle et al used the NISTmAb and infliximab in a comparative study and achieved RSD values of 0.05% for the apparent pI value and 1.3% for the percentage area of the NISTmAb main peak, whereas for the infliximab main peak, the reported RSD values were 0.04% and 2.4% for pI and percentage area, respectively.…”
Section: Cief and Iciefmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant proteins will show heterogeneity in different expression systems and under different production process conditions, contributed by the post-translational modifications (PTMs) [ 16 , 17 ]. The isoelectric point (pI) is a powerful tool to determine the presence of protein isoforms [ 18 ]. Furthermore, it is noted that the isoelectric point is one of the prime keys for understanding various biochemical properties of protein sequences [ 19 , 20 ].…”
mentioning
confidence: 99%